Evaluation of the Youth Contract wage incentive : wave two research.: wave two research. (February 2014) - Coleman, Nick, 1965-; McGinigal, Stephen; Thomas, Andrew, 1954 December 24; Fu, Emily; (Research executive), Hingley, Sarah
No abstract available